(untitled) (Biodiversitas Journal of Biological Diversity, 2008)
Actinomycetes is a major microbial group observed in soil, and contributes to nutrient cycling. This study is intended to verify physiological characters and phosphate solubilizing ability of Actinomycetes isolated from soil of Raja Ampat, West Papua. Most of isolates (RCW16-9, RCW16-8, W5-6, RCW25-1, RCW26-5, W28-4, W3-1, W3-7, W17-7, and W10-1) belonged to Streptomyces genera. The isolates produce clear zone in Pivoskaya after 3 days incubation. The liquid growth of this isolate rapidly utilizes glucose, and after 24 days of incubation almost 95% glucose was consumed. Decrease of pH from 6.1 to 4.3 may stimulate dissolution of calcium phosphate, and about 21 mg/L-P was observed in bulk solution. An increase of phosphomonoesterase activity during incubation is concomitant with the release of orthophosphate into bulk solution. Acidity of cultures increased may stimulate solubilization of calcium phosphate. Most strains produce phosphomonoesterase enzyme, indicating that actinomycetes are important soil microbes responsible for mediation and stimulation of both inorganic and organic phosphate dissolution. Physiological and biomass growth character of phosphate solubilizing actinomycetes could be important taxonomic indicator for identifying and grouping soil actinomycetes. Â© 2008 Jurusan Biologi FMIPA UNS Surakarta Key words: Actinomycetes, phosphate solubilizer, phosphomonoesterase, glucose